The Home of the Senses: insights on Rudolf Olgiati’s Houses - Gil Guinea, Luis; Román Santiago, Ignacio (Cuadernos de Proyectos Arquitectónicos, 2019)
Abstract In the period between 1939 and 1992, Rudolf Olgiati built around 150 houses and small residential complexes in a very limited area of Graubünden. He developed a truly unique way of doing things, defining a personal language that has transcended his local context. This paper hypothesises that his work also contains a valuable lesson that can be applied in many other places. It is a matter of arguing how, from the harmony of the architectural elements, the materials, the colour and the furniture, and through an exceptional sensitivity to the perceptions of the inhabitant, Olgiati manages to elevate the house above the architectural object and transform it into a home for the mind as well. To this end, the article establishes the relationship between Olgiati’s domestic architecture and the philosophical idea of home, as described by Bachelard in The Poetics of Space. In 1957, the year the essay was published, Olgiati began to build his first houses. Determining aspects in his training are pointed out, selected elements of his architecture analysed, with the aim of understanding his character and his sensitivity, and identifying the issues that tell us more about the quality of these houses. All of them touch on with emotional distinction the close, the concrete, and the useful, through the sensitive application of the universal and the abstract. Perhaps then, like Bachelard’s home, they become a nest for memories and emotions, an intimate place for memory and dreams, an instrument that allows the inhabitant, in the words of the philosopher, “to face the cosmos”.